Motion, transfer and transformation : the grammar of change in lowland Chontal - O'Connor, Loretta (Studies in language companion series ;, 2007)
Typologies are critical tools for linguists, but typologies, like grammars, are known to leak. This book addresses the question of typological overlap from the perspective of a single language. In Lowland Chontal of Oaxaca, a language of southern Mexico, change events are expressed with three types of predicates, and each predicate type corresponds to a different language type in the well-known typology of lexicalization patterns established by Talmy and elaborated by others. O'Connor evaluates the predictive powers of the typology by examining the consequences of each predicate type in a vari.